The Impact of Artificial Intelligence on Supply Chain Management Title - Mežnar, Dušan; Urh, Benjamin (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Artificial intelligence is increasingly changing various aspects of business operations. In the field of supply chain management, it is being used to analyse data and forecast demand, optimise logistics and transport routes, and identify inefficiencies. The result is better responsiveness to fluctuations in demand, shorter delivery times, and lower costs. The basic aim of this article is to investigate and analyse the use of artificial intelligence in supply chain management using the WoS database. The basic objective is to conduct an analysis of the impact of artificial intelligence on supply chain management performance, to determine which types of artificial intelligence improve supply chain management efficiency and which areas have the potential for improvement, and to examine the impact of the application of artificial intelligence on supply chain management performance.